The Effect of Problem Based Learning Model in Improving Students Argumentation Skills: Systematic Literature Review - Okmarisa, Happy; Lestari, Niken Ayu; Ariani, Listia (Universitas Pendidikan Mandalika, 2025)
The purpose of this study is to determine the application of the Problem Based Learning (PBL) learning model affects the ability in learning chemistry in high school. The research was conducted through a literature review from various reliable sources published in 2020-2024. Compared to the traditional learning model, the application of PBL improves students' argumentation skills consistently. This improvement can be seen from the increase in post-test mean scores, N-Gain scores, and mastery of argumentation metrics such as claims, justifications, and refutations. In addition, the PBL model showed better results when used together with learning media, STEM approaches, or group discussions. Therefore, PBL helps students in problem-solving, critical thinking, and scientific communication skills in chemistry learning.